2022
DOI: 10.1038/s41598-022-06213-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermal performance of Maxwell hybrid nanofluid boundary value problem in vertical porous surface via finite element approach

Abstract: The study of thermo-physical characteristics is essential to observe the impact of several influential parameters on temperature and velocity fields. The transportation of heat in fluid flows and thermal instability/stability is a charming area of research due to their wider applications and physical significance because of their utilization in different engineering systems. This report is prepared to study thermal transportation in Maxwell hybrid nanofluid past over an infinite stretchable vertical porous she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 37 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…The suspension of tiny solid particulate in liquids is an effective method of increasing the thermal conductivity of liquids and thereby enhances the heat transference phenomenon. Using these kinds of liquids, several investigators explored the features of heat transferal 1 7 . On the other side, heat transfer is enhanced using the extended surface.…”
Section: Introductionmentioning
confidence: 99%
“…The suspension of tiny solid particulate in liquids is an effective method of increasing the thermal conductivity of liquids and thereby enhances the heat transference phenomenon. Using these kinds of liquids, several investigators explored the features of heat transferal 1 7 . On the other side, heat transfer is enhanced using the extended surface.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical approach is adopted as a finite element scheme 52 (FEM) 17 , 18 to compute the solution of highly ODEs (non-linear). The domain of current model is broken into small segments called finite element scheme.…”
Section: Numerical Techniquementioning
confidence: 99%
“…In another study, Takabi and Shokouhmand [ 30 ] concluded that using hybrid nanofluids enhances the heat transfer rate as compared to pure water and nanofluids, but it has a negative effect on the friction factor and appears to be significantly offset by the pressure drop loss. Nowadays, a significant number of studies on hybrid nanofluids have been published by past scholars, including Zainal et al [ 31 ], Khashi’ie et al [ 32 ], Waini et al [ 33 ], and Algehyne et al [ 34 ].…”
Section: Introductionmentioning
confidence: 99%